(untitled) (Educational Knowledge, 2025)
Evaluation is inherently formative and a fundamental part of the teaching-learning process. One of the key components of both teaching and formative assessment is feedback. This study aimed to identify graduate students’ perceptions regarding feedback as a teaching and formative assessment strategy. Adopting a qualitative phenomenological approach, the research sought to describe and understand the phenomenon from both individual and collective perspectives. Purposeful sampling included individuals who had completed a Master’s in University Teaching and had experience with feedback as a pedagogical strategy. A survey with 11 questions was used, revealing that feedback should be considered a core learning tool, one that plays a central role in didactic development.